Split Skin Grafting the Heart: A Simple Solution for a Complex Reconstructive Challenge. Issue 8 (19th August 2021) - Cochrane, Elliott; Morritt, Andrew
Abstract : Summary: We present the interesting case of an 87-year-old woman who underwent debridement of chest wall osteoradionecrosis (ORN) that arose following radiotherapy for breast cancer. Debridement left a complex defect with exposed myocardium and parietal pleura. An extensive surgical history, compromised physiological reserve, and the patient's desire not to undergo major reconstructive surgery limited the reconstructive options. Ultimately, a split skin graft (SSG) was applied directly to the heart and pleura to obtain wound closure. We believe this is the first report of an SSG being applied directly onto the myocardium to achieve stable soft tissue cover